Ultralow interface resistance in porous transport electrode for efficient polymer electrolyte membrane water electrolysis at low Ir loading - Lee, Jegon; Kim, Sol; Kim, Jin Young; Jang, Jong Hyun; Park, Hee-Young; Seo, Bora (Elsevier BV, 2025)
Achieving high-efficiency polymer electrolyte water electrolysis (PEMWE) with minimal use of precious metals remains a critical challenge for clean hydrogen production. A major bottleneck is the interface resistance at the membrane-electrode-diffusion layer, especially under low catalyst loadings. Here, a simple yet powerful catalyst-integrated diffusion layer fabrication strategy is presented that enables ultralow interface resistance even at reduced Ir loadings. By directly synthesizing a TiO2-supported IrOx catalyst (TiO2-IrOx) onto Ti felt through a single-step calcination, a porous transport electrode (PTE) is constructed and serves as a high-performance anode. At an optimized Ir loading of only similar to 0.12 mg(Ir) cm(-2), the TiO2-IrOx PTE exhibits an exceptional current density of 2.54 A cm(-2) at 1.9 V, outperforming state-of-the-art benchmark electrodes. Moreover, even after a long-term durability test with ultralow loadings (<0.1 mg(Ir) cm(-2)), the ultralow interface resistance of the TiO2-IrOx PTE is maintained. As a result, the TiO2-IrOx PTE achieves a significantly high mass activity of 20 A mg(Ir)(-1) at 1.9 V, far surpassing conventional Ir-based electrodes. This work provides a compelling pathway toward reducing dependence on scarce platinum-group metals without compromising the performance of the PEMWE system.